Acyl migration versus epoxidation in gold catalysis: facile, switchable, and atom-economic synthesis of acylindoles and quinoline derivatives - Tian, Xianhai; Song, Lina; Rudolph, Matthias; Rominger, Frank; Oeser, Thomas; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2020)
We report a switchable synthesis of acylindoles and quinoline derivatives via gold-catalyzed annulations of anthranils and ynamides. α-Imino gold carbenes, generated in situ from anthranils and an N,O-coordinated gold(III) catalyst, undergo electrophilic attack to the aryl π-bond, followed by unexpected and highly selective 1,4- or 1,3-acyl migrations to form 6-acylindoles or 5-acylindoles. With the (2-biphenyl)di-tert-butylphosphine (JohnPhos) ligand, gold(I) carbenes experienced carbene/carbonyl additions to deliver quinoline oxides. Some of these epoxides are valuable substrates for the preparation of 3-hydroxylquinolines, quinolin-3(4H)-ones, and polycyclic compounds via facile in situ rearrangements. The reaction can be efficiently conducted on a gram scale and the obtained products are valuable substrates for preparing other potentially useful compounds. A computational study explained the unexpected selectivities and the dependency of the reaction pathway on the oxidation state and ligands of gold. With gold(III) the barrier for the formation of the strained oxirane ring is too high; whereas with gold(I) this transition state becomes accessible. Furthermore, energetic barriers to migration of the substituents on the intermediate sigma-complexes support the observed substitution pattern in the final product.
First published: 17 October 2019
Gesehen am 15.01.2020